Development of a QR Code-Based Physical Education Module with Basic Techniques Floor Gymnastics at State Senior High School 4 Lebong - Darsi, Helvi; Salman, Erick; Zulbahri, Zulbahri; Surahman, Fadli (JETL (Journal of Education, Teaching and Learning), 2025)
This research is motivated by the low interest and learning outcomes of students in participating in PJOK learning, especially the material on basic floor gymnastics techniques. The purpose of this research is for students to be happy and excited in participating in the PJOK learning process through the use of QR Code-based floor gymnastics modules to improve the learning outcomes of basic floor gymnastics techniques in students of SMA Negeri 4 Lebong. This research uses the Research and Development (R&D) method with the Dick and Carey model approach. Data collection techniques include interviews, observations, and questionnaires. Data were analyzed based on validation from language, material, and media experts. The results of the study show that: (1) the quality of the module from the validity aspect is classified as valid, with a score from language experts of 0.86; material experts 0.81; and media experts 0.817. (2) From the practicality aspect, the module is classified as very practical, with a teacher response of 4, one to one 3.9, and small group 4.0. The conclusion of this study shows that the QR Code-based PJOK module is suitable for use as a media for learning floor gymnastics. The implication of this research is that the use of QR Code technology can be an innovative alternative in PJOK learning, and is recommended for further development in other materials in the PJOK curriculum.